Performance Evaluation of Convolutional Neural Networks with oneAPI and OpenMP for Network Intrusion Detection - Oliveira, Rafael Rodrigues; Leão, Thiago Augusto Demeto; Freitas, Henrique Cota de (Anais Estendidos do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2025: Anais Estendidos do XXVI Simpósio em Sistemas Computacionais de Alto DesempenhoDO - 10.5753/sscad_estendido.2025.16684, 2025)
The accelerated evolution in the Machine Learning (ML) field has made the use of hardware solutions indispensable for training and inferring models. This article presents the performance evaluation of three implementations of a Convolutional Neural Network: a sequential version and two parallel versions, one using Intel oneAPI and the other with OpenMP, all running on the CPU. The comparative analysis is based on a network intrusion dataset (NSL-KDD), focusing on speedup and scalability. It shows that the implementation using Intel® oneAPI achieves the best performance compared to the sequential and OpenMP versions.